NUTRITIONAL STATUS OF PRIMARY SCHOOL CHILDREN IN ABBOTTABAD - Siddique, Saadia; Ayub, Muhammad; Shore, Najla; Tariq, Usman; Zaman, Shakila (Journal of Ayub Medical College Abbottabad, 2013)
Background: In Abbottabad district, with the vast poverty stricken rural majority and 80% literacy rate, primary-level education faces great influx of students. This study was carried out to see the nutritional status of children 5-10 years of age attending primary schools of Abbottabad. Methods: This was a descriptive, cross-sectional study carried out in June 2009 on 400 schoolchildren of 5-10 years of age from three randomly selected primary schools of Abbottabad. After informed consent by the parents/ teachers, a semi-structured Performa/questionnaire was filled for each child. Anthropometric measurements were recorded. Correlation of age of the child with height, and weight was calculated. Result: The nutritional status of the study children was particularly optimum; 90% children were in optimal nutritional status and had sound skeletal growth irrespective of their socioeconomic background. There was a significant correlation of nutritional status and skeletal growth of children with parents' socioeconomic status. There was a direct correlation between height and weight of children, and their age. Conclusion: Anthropometric measurements indicate a high majority of children in healthy status despite the overall poor setup. Keywords: Nutrition, Malnutrition, Child health, Stunting, BMI, Risk factors, Abbottabad